Neurostimulation on lumbosacral nerves as a new treatment for spinal cord injury impairments and its impact on cortical activity: a narrative review - Marques Dantas, Rodrigo Lantyer; Vilela, Diego N.; Melo, Mariana Cardoso; Fernandes, Gustavo; Lemos, Nucelio; Faber, Jean (Frontiers in Human Neuroscience, 2024)
Spinal cord injury (SCI) can cause significant motor, sensory, and autonomic dysfunction by disrupting neural connections. As a result, it is a global health challenge that requires innovative interventions to improve outcomes. This review assesses the wide-ranging impacts of SCI and focuses on the laparoscopic implantation of neuroprosthesis (LION) as an emerging and promising rehabilitation technique. The LION technique involves the surgical implantation of electrodes on lumbosacral nerves to stimulate paralyzed muscles. Recent findings have demonstrated significant improvements in mobility, sexual function, and bladder/bowel control in chronic SCI patients following LION therapy. This manuscript revisits the potential physiological mechanisms underlying these results, including neuroplasticity and modulation of autonomic activity. Additionally, we discuss potential future applications and amendments of LION therapy. This study emphasizes the potential of neuromodulation as a complementary approach to traditional rehabilitation, that can provide a beacon of hope for improving functionality and quality of life for individuals with SCI.